Beyond sex: the effects of testosterone on visuomotor performance in men and women - Smeha, Nicole; Gorbet, Diana J.; Edgell, Heather; Macpherson, Alison K.; Sergio, Lauren E. (Frontiers in Human Neuroscience, 2026)
IntroductionThe ability to perform visually-guided motor tasks requires the transformation of visual information into programmed motor outputs. When the guiding visual information does not align spatially with the motor output, the brain processes rules to integrate somatosensory information into an appropriate motor response. Performance on such rule-based, “cognitive-motor integration” (CMI) tasks has been shown to be affected by sex, age, and in several neurologic conditions. The present study sought to (1) expand on these findings by examining whether such performance differences are related to levels of sex steroid hormones, and (2) characterize the relationship between hormone levels and any structural differences in brain regions responsible for complex motor control.MethodsThirty-six healthy individuals (18 females) underwent MRI scanning to acquire anatomical brain images. They performed two touchscreen-based eye–hand coordination tasks, including a standard direct interaction task and one which involved CMI; target location and motor action were dissociated in the CMI task. Saliva samples collected on the day of testing were used to determine estrogen, progesterone, and testosterone levels.ResultsMultiple regression analyses revealed age to be a small but significant predictors of performance in a CMI condition with visual feedback reversal. We found that after accounting for this age effect, testosterone was a significant predictor of CMI performance in this group. We also observed that the relationship between testosterone levels and complex performance was related to grey matter thickness and volume in visuomotor control regions.ConclusionThese data suggest that underlying brain networks controlling simultaneous thought and action may differ as a function of sex steroid hormone concentrations, and that small performance declines emerge in the working-age years.